Evidence for nevirapine bioactivation in man: Searching for the first step in the mechanism of nevirapine toxicity. - Caixas, U (2012)
Nevirapine (NVP) is a non-nucleoside reverse transcriptase inhibitor used against human immunodeficiency virus type-1 (HIV-1), mostly to prevent mother-to-child HIV-1 transmission in developing countries. Despite its clinical efficacy, NVP administration is associated with a variety of toxic responses that include hepatotoxicity and skin rash. Although the reasons for the adverse effects of NVP administration are still unclear, increasing evidence supports the involvement of metabolic activation to reactive electrophiles. In particular, Phase II activation of the NVP metabolite 12-hydroxy-NVP is thought to mediate NVP binding to bionucleophiles, which may be at the onset of toxicity. In the present study, we investigated the nature and specific locations of the covalent adducts produced in human serum albumin and human hemoglobin by reaction in vitro with the synthetic model electrophile 12-mesyloxy-NVP, used as a surrogate for the Phase II metabolite 12-sulfoxy-NVP. Multiple sites of modification were identified by two different mass spectrometry-based methodologies, liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) and matrix-assisted laser desorption ionization tandem mass spectrometry (MALDI-TOF-TOF-MS). These two distinct methodologies, which in some instances afforded complementary information, allowed the identification of multiple adducts involving cysteine, lysine, tryptophan, histidine, serine, and the N-terminal valine of hemoglobin. Tryptophan, which is not a common site of covalent protein modification, was the NVP-modified amino acid residue detected in the two proteins and consistently identified by both LC-ESI-MS/MS and MALDI-TOF-TOF-MS. The propensity of tryptophan to react with the NVP-derived electrophile is further emphasized by the fact that human serum albumin possesses a single tryptophan residue, which suggests a remarkable selectivity that may be useful for biomonitoring purposes. Likewise, the NVP adduct with the terminal valine of hemoglobin, detected by LC-ESI-MS/MS after N-alkyl Edman degradation, appears as an easily assessed marker of NVP binding to proteins. Our results demonstrate the merits and complementarity of the two MS-based methodologies for the characterization of protein binding by NVP and suggest a series of plausible biomarkers of NVP toxicity that should be useful in the monitoring of toxicity effects in patients administered NVP.